PENGARUH DUKUNGAN SOSIAL, KONSEP DIRI, DAN STRATEGI PENGATURAN DIRI DALAM BELAJAR TERHADAP PRESTASI AKADEMIK - Situmorang, Zervina Rubyn Devi; Latifah, Melly (Jurnal Ilmu Keluarga dan Konsumen, 2014)
Academic achievement is influenced by many factor such as internal factor and external factor. The purpose of this study was to analyze child and family characteristic, social support, self-concept, self-regulated learning (SRL) strategies, and academic achievement; to examine the effect of social support and self-concept on selfregulated learning strategies; and to examine the effect of social support, self-concept, and self-regulated learning strategies on student’s academic achievements. Samples of 150 junior high school students in Bogor Region were used in this study. Cluster random sampling was used in selection of those junior high schools. Partial Least Square analysis showed that self-concept had a significant effect on SRL strategies but it was not significant on social support. Parent's education were negatively affecting to academic achievement. Social support and selfconcept also had no effect on student’s academic achievement. However, the effect of SRL strategies onstudent’s academic achievement were found to be positively significant.